Features of the Use of Collateral Frameworks in Central Bank Operations - Ghazaryan, Amasya (Bulletin of Yerevan University G: Economics, 2022)
The aim of the current work is in the discovery and analysis of collateral criteria applied in the operations of central banks. The importance of collateral criteria is underlined in the context of the security and risk management of central banks’ balance sheet, which is a cornerstone in the formation, strengthening and development of central bank credibility. Peculiarities of collateral criteria were analyzed in the context of three main functions of central banks known in the literature- market maker of last resort, monetary policy implementer, lender of last resort. Particularly, three main groups of criteria were discussed- market participants, quantity and quality of collateral, the analysis of which revealed differences in application of collateral criteria contingent upon central bank functions and economic situations. Besides the aforementioned, the mechanisms of effects of changes in collateral criteria were considered and some empirical results of the literature were discussed. The paper concludes that differentiation in the collateral criteria by central bank functions, ceteris paribus, allows avoiding unnecessary risk accumulation and paves way for the improvement of the quality of macroprudential and monetary policy implementation.